Dampak Strategi Pasar Moderen terhadap Pedagang Tradisional di Kota Metro - Ambariyani (Bulletin of Community Engagement, 2024)
In Metro City, there are modern markets and traditional traders. Modern markets in Metro City have sprung up quite a lot. Almost in every corner of Metro City there are modern markets such as Alfamart, Indomart, PB Swalayan, Candra and others. With various strategies used by modern markets, the position of traditional traders will gradually be eliminated or less in demand by the community. The marketing strategy used by modern markets has an impact on traditional traders. The purpose of this study is to determine the strategies used by modern markets and the impact of the strategies used by modern markets on traditional traders in Metro City. This type of research is field research. This study uses a qualitative method. The primary data sources in this study are traditional traders, modern market employees and several government figures in Metro City. The results of this study are the strategies used by modern markets, namely product strategy, price strategy, place strategy and promotion strategy. By implementing product strategy, place strategy, and promotion strategy, traditional traders in Metro City have a negative impact, namely decreasing purchases or public interest in shopping at traditional stalls or traders and with the advancement of the times, people's lifestyles, especially in shopping, have changed. Meanwhile, the price strategy has not had a bad impact on traditional traders, because there are still some people who consider price as an alternative to shopping or buying the products they need and there is still a bargaining process between sellers and buyers. This means that the price strategy still has a positive impact on traditional traders in Metro City.